The factors affecting the succession of female descendants in family business in Thailand - โกมุทพงศ์, ลภัสรดา; พสุนนท์, ประสพชัย (Business Administration and Management Journal Review, 2016)
This study aims to examine the factors affecting the succession of female descendants in family business in Thailand. The population in this study includes 100 female descendants in YEC (Young Entrepreneur Chamber of Commerce). The data are collected by using questionnaires. The statistics for analyzing are frequency, average, standard deviation and stepwise multiple regression analysis with the significant level of 0.05. The result shows that factors affecting the succession of female descendants in family business in Thailand are commitment of female descendants to family business and entrepreneurship. In the future, the result can be applied for encouraging business growth and development.